COMBINATION OF PROBLEM BASED LEARNING MODEL AND INVESTIGATION GROUP FOR ENVIRONMENT SUBJECT - Marhamah Marhamah (Journal Of Biology Education Research (JBER), 2021)
Education has an important role in influencing one's attitudes, including attitudes towards the environment. The purpose of writing is to explain how learning through a combination of Problem Based Learning and Group Investigation models in improving attitudes towards the environment. Investigative activities to find out the surrounding environmental problems followed by the process of solving problems encountered during the investigation are a series of learning processes that will foster concern for environmental problems. Knowledge gained from direct experience of real problems found will affect a person's behavior or attitude.